Pengaruh Suhu Perendaman Dalam Larutan Garam Terhadap Kandungan Kalsium Oksalat Tepung Keladi (Xanthosoma Sagittifolium) - Nathasya br Lahi, Putri; Suparthana, I Putu; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p05, 2023)
The potential for the use of taro as a food ingredient and raw material for the food industry has enormous opportunities, given the very affordable price of taro and its processing into flour which is quite simple for the community and industry to do. This study aims to determine the effect of salt (NaCl) solution temperature which used for immersion of the corms (Xanthosoma sagitifolium) to decrease the oxalate compound. The experiment was designed as a Completely Randomized Design with 28°C (room temp.), 60°C, 70°C, 80°C and 90°C as the treatments. All treatments were repeated 3 times so that 15 experimental units were obtained. The data were analyzed by using a variance analysis tool, and for the treatment showing significant effect was continued to be analyzed by using Duncan Multiple Range Test. The results indicated that temperature of salt solution has a significant effect on water content, calcium oxalate, yield and color of the flour which proceed from the corms. The flour produced from the corm which previously immersed in salt solution with temperature of 90°C has calcium oxalate content of 0.38%.